The magnitude of Public Accounts Committee's (PAC's) work in reviewing and reporting on state government's financial statements / Rose Shamsiah Samsudin and Nafsiah Mohamed - Nafsiah, Mohamed (Accounting Research Institute (ARI) & Faculty of Accountancy, 2009)
This paper examines the function of the Public Accounts Committee (PAC) of all the eleven states in Peninsula Malaysia. The concept of PAC oversight exists as an essential effect to the legislature's process, where oversight function compliments rather than hampers the effective performance of financial accountability with which the executive is entrusted. A preliminary study was carried out on one 2005 PAC Report of a state and it was found that the Report was made based on the 2002 audited financial statements. Further analysis on the 2005 PAC Report of the other ten states reveals that the PAC Reports of all these states were outdated because they review non-current audited financial statements. Some states even reviewed and made reports on a few years' financial statements concurrently. Thus, the significance of the PAC Report is at stake as the comments and recommendations made might not be relevant.